- Thread starter
- #1

2x + 3y = 5

5x - 2y = - 16

I worked out;

y = 1/3(5 - 2x) and combined them

y = 5x - 2/3(5 - 2x) = - 16 then I worked out the brackets

y = 5x - 10/3 + 4/3x = - 16. From here I become somewhat misunderstood as to the way things are done.

I think from here I require to convert the equations into a linear equation without the fractions, but am unsure?

(5 + 4/3)x - 10/3 = - 16. I don't know what the rule is to get to this stage from the last stage above?

If I multiply out the bracket above I get;

5x + x - 2 = - 16

6x = - 16 + 2

6x = -14

x = - 2.33

Now somewhere I am misunderstanding something because x = 2.

I also know that y = 3, but until I am clear on the method to find x there is no point me trying to go forward from finding x?

Any help much appreciated

Kind regards

Casio